Impact of instructional design on students’ critical thinking and engagement in online English reading classes: mediating role of motivation and moderating role of language proficiency - Huang, Qiuyang; Muhamad, Mohd Mokhtar; Che Nawi, Nur Raihan (Frontiers in Psychology, 2025)
This study investigates the association between instructional design, students’ critical thinking skills, and student engagement, as well as the mediating role of motivation and the moderating role of language proficiency. Data were collected from 380 students using a random sampling technique. A structured questionnaire was employed as the research instrument, and data were analyzed through structural equation modeling (SEM). The findings indicate that inquiry-based instructional design shows a significant positive relationship with both critical thinking skills and student engagement, whereas traditional instructional design shows a negative relationship. The blended instructional design demonstrates a positive relationship, though to a lesser extent than the inquiry-based approach. Moreover, motivation mediates the relationship between instructional design and both critical thinking skills and student engagement. Language proficiency moderates the relationship between instructional design and critical thinking skills, but not student engagement.